Variation in caprine milk composition and coagulation as affected by udder health indicators. (November 2019) - Stocco, Giorgia; Pazzola, Michele; Dettori, Maria L.; Cipolat-Gotet, Claudio; Summer, Andrea; Vacca, Giuseppe M.
Abstract: Milk lactose, pH, somatic cell count (SCC), bacterial count and NaCl are indirect markers of the mammary gland status; they can be used to screen milk quality and its technological properties. The variability of milk composition and coagulation properties from 1272 individual goat milk samples as a function of the udder health indicators was investigated. High lactose concentrations were associated with reduced coagulation time, but weakened curd firmness traits. High pH values impaired coagulation, while high SCC had delayed coagulation time but reduced curd-firming rate. Samples with high bacterial count were characterised by softer curds, but had faster curd-firming and larger syneresis rates. High concentrations of NaCl were associated with reduced fat, protein, and casein content, and impaired coagulation traits. These results show that the concurrent analysis of these markers can be highly informative and suitable to monitor the quality of milk destined for cheese-making.